Implementasi Kegiatan Ekstrakurikuler Dalam Mengembangkan Profil Pelajar Pancasila Pada Siswa SMPN Satap 3 Boawae - Maria Theresia Peti Bhengu; fransiskus xaverius bares ushiro tandafatu; doroste yenita dhange; novia mariana dungan; maria elisabet lewar; anastasia ea (Jurnal Pembelajaran dan Pendidikan Dasar, 2026)
This study aims to analyze the implementation of extracurricular activities in developing the Pancasila Student Profile among students at SMPN Satap 3 Boawae. A qualitative approach with a descriptive research design was employed. Research subjects were selected through purposive sampling, consisting of one principal, three teacher coaches, and eight students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model (data reduction, data display, and conclusion drawing). The findings indicate that mandatory extracurricular activities (Scouting) and elective programs (Literacy, Numeracy, Sports, and Arts), scheduled daily at 13.00 WITA, significantly contribute to developing the dimensions of the Pancasila Student Profile. Specifically, literacy and numeracy programs strengthen the critical thinking dimension; sports and arts activities promote creativity and collaboration (gotong royong); while Scouting builds independence and discipline. Furthermore, the school culture, including the 3S movement (Smile, Greet, Salute), reinforces the dimension of faith and piety. However, the primary challenge remains the fluctuation of participation motivation among some students. This study concludes that extracurricular activities serve as an effective strategic instrument for holistically internalizing Pancasila character values for students in a one-roof school setting.